2016
DOI: 10.1371/journal.pone.0147406
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Facilitators Associated with Non-Surgical Treatment Use for Osteoarthritis Patients in Orthopaedic Practice

Abstract: IntroductionInternational evidence-based guidelines for the management of patients with hip and knee osteoarthritis (OA) recommend to start with (a combination of) non-surgical treatments, and using surgical intervention only if a patient does not respond sufficiently to non-surgical treatment options. Despite these recommendations, there are strong indications that non-surgical treatments are not optimally used in orthopaedic practice. To improve the adoption of non-surgical treatments, more insight is needed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 32 publications
3
55
0
3
Order By: Relevance
“…Our results are in line with previous studies that reported an underuse of non‐surgical treatment options in patients with knee OA (Brand et al, ; Hoogeboom et al, ; Smink et al, ; Snijders et al, ). In addition, Hofstede et al found similar barriers for referral to non‐surgical treatment for OA patients in orthopaedic practice (Hofstede et al, ). Egerton et al described in a systematic review similar barriers to the management of osteoarthritis in primary care GPs: GPs tend to trivialize the problem and believe OA to be inevitable and lower priority than other health conditions which may lead to under management of the condition; a lack of knowledge regarding OA guidelines; clinicians' perceptions about the disease, patient adherence and the treatment effectiveness may all lead to variable practice at odds with the recommendations (Egerton, Diamond, Buchbinder, Bennell, & Slade, ).…”
Section: Discussionmentioning
confidence: 99%
“…Our results are in line with previous studies that reported an underuse of non‐surgical treatment options in patients with knee OA (Brand et al, ; Hoogeboom et al, ; Smink et al, ; Snijders et al, ). In addition, Hofstede et al found similar barriers for referral to non‐surgical treatment for OA patients in orthopaedic practice (Hofstede et al, ). Egerton et al described in a systematic review similar barriers to the management of osteoarthritis in primary care GPs: GPs tend to trivialize the problem and believe OA to be inevitable and lower priority than other health conditions which may lead to under management of the condition; a lack of knowledge regarding OA guidelines; clinicians' perceptions about the disease, patient adherence and the treatment effectiveness may all lead to variable practice at odds with the recommendations (Egerton, Diamond, Buchbinder, Bennell, & Slade, ).…”
Section: Discussionmentioning
confidence: 99%
“…We use empirical data here from two previously published studies, which are performed at different moments in time: one involving implementation28 29 and one involving de-implementation30 31 among Dutch orthopaedic surgeons. The implementation study aimed to identify factors influencing the implementation of a step-wise strategy of non-surgical therapy for patients with hip and knee osteoarthritis (OA) (including medication and referral guidelines) before undertaking surgical therapy 14.…”
Section: Empirical Datamentioning
confidence: 99%
“…The qualitative analysis was performed using the software program ATLAS.ti (version 7.5.16). A total of 55 factors were identified from the literature [21,22,25,36,46] for orthopaedic surgeons and patients. Besides, four factors were added based on the interviews among orthopaedic surgeons and patients.…”
Section: Methodsmentioning
confidence: 99%